Reproductive Biology of Pterygoplichthys pardalis in the Air Hitam River Payung Sekaki District, Riau Province - Flora Monica Pinem; Chaidir P Pulungan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Pterygoplichtys pardalis has known as sapu-sapu fish. It is commonly present in the Air Hitam River. To understand the reproductive biology of this fish, a research has been conducted on February to May and November 2015. Fish samples were obtained from the Air Hitam River. Parameters investigated were fish morphology, sex ratio, maturity level, fecundity and the relationship between fecundity, length and weight. Samplings were done at three stations, in the in the upstream (Station I), middle (Station II), and downstream (Station III) of the river. Totally 169 fishes (75 males and 94 females) were captured. Sex ratio between male and female was 1:1.2. The Gonado Somatic Index (GSI) of male was 0.0022% -2.6% and that of the female was 0.03-3.4%. Egg diameter was 1.5 -3.2 mm. The fecundity is around 5,351-48,980 eggs/fish. The relationship between fecundity and standart length was y= 2.056x -0.548, fecundity and body weight was y= 0.863x +2.290. The water quality parameters are as follows: temperature 27-28.5°C, turbidity 15-22 NTU, the depth of the water 0.75-0.80 m, the width of the river 8.06 m, current speed 0.15-0.44 m/s, pH 6-9, DO 2.5-3 mg/L. Data on water quality parameters indicate that water quality in the Air Hitam River is able to support the life of the fish and the fish may reproduce well.Keyword: Pterygoplichtys pardalis, reproduction, sex ratio, GSI, fecundity, Air Hitam River